Keratin 17 Is Required for Lipid Metabolism in Keratinocytes and Benefits Epidermal Permeability Barrier Homeostasis - Pang, Bingyu; Zhu, Zhenlai; Xiao, Chunying; Luo, Yixin; Fang, Hui; Bai, Yaxing; Sun, Zhongbin; Ma, Jingyi; Dang, Erle; Wang, Gang (Frontiers in Cell and Developmental Biology, 2022)
The epidermal barrier refers to the stratum corneum, the uppermost layer of the skin, and constitutes the first line of defense against invasion by potentially harmful pathogens, diminishes trans-epidermal water loss, and plays a crucial role in the maintenance of skin homeostasis. Keratin 17 (K17) is a type I epithelial keratin with multiple functions, including in skin inflammation, epithelial cell growth, protein synthesis, and tumorigenesis. However, the relationship between K17 and the skin barrier has yet to be systematically investigated. In this study, we found that acute disruption of the epidermal permeability barrier led to a rapid increase in epidermal K17 expression in vivo. Krt17 gene deficiency in mice resulted in decreased expression of lipid metabolism-related enzymes and antimicrobial peptides, while also delaying epidermal permeability barrier recovery after acute disruption. Adenovirus-mediated overexpression of K17 enhanced, whereas siRNA-mediated knockdown of Krt17 inhibited, the expression of fatty acid synthase (FASN) and that of the transcription factors SREBP-1 and PPARγ in vitro. We further confirmed that K17 can facilitate the nuclear transportation of SREBP-1 and PPARγ and promote lipid synthesis in keratinocytes. This study demonstrated that K17 contributes to the restoration of the epidermal permeability barrier via stabilizing lipid metabolism in keratinocytes.